2001
DOI: 10.1017/s0952523801184026
|View full text |Cite
|
Sign up to set email alerts
|

A cGMP-gated channel subunit in Limulus photoreceptors

Abstract: The phototransduction cascade in invertebrate photoreceptors has not been fully elucidated. It has been proposed that in Limulus ventral photoreceptor cGMP is the intracellular second messenger that directly controls the gating of the light-dependent channels (Johnson et al., 1986: Bacigalupo et al., 1991). Recently, a putative cGMP-gated channel cDNA, Lcng1, has been cloned from Limulus and shown to be expressed in the brain and the ventral eye (Chen et al., 1999). In this study, we sought to more specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Other studies have suggested as many as three different kinds of light-sensitive channels possibly operating in parallel, controlled by distinct G protein-mediated pathways: one signaling via PLC and InsP 3 , a second via GC, and a third via adenylate cyclase (Dorlochter and Stieve, 1997; Nasi et al, 2000). Consistent with the electrophysiological evidence mentioned above, a cGMP-gated cation channel homologous to the vertebrate CNG channels has been cloned and immunolocalized to the microvillar membrane (Chen et al, 2001). A Limulus trp homolog was also found in the mRNA from the ventral photoreceptor (Bandyopadhyay and Payne, 2004).…”
Section: Invertebratessupporting
confidence: 56%
See 1 more Smart Citation
“…Other studies have suggested as many as three different kinds of light-sensitive channels possibly operating in parallel, controlled by distinct G protein-mediated pathways: one signaling via PLC and InsP 3 , a second via GC, and a third via adenylate cyclase (Dorlochter and Stieve, 1997; Nasi et al, 2000). Consistent with the electrophysiological evidence mentioned above, a cGMP-gated cation channel homologous to the vertebrate CNG channels has been cloned and immunolocalized to the microvillar membrane (Chen et al, 2001). A Limulus trp homolog was also found in the mRNA from the ventral photoreceptor (Bandyopadhyay and Payne, 2004).…”
Section: Invertebratessupporting
confidence: 56%
“…Even in rods and/or cones, G α11 and PLCβ4 are present (Ferreira and Pak, 1994; Peng et al, 1997) but are apparently not involved in the phototransduction pathway (Jiang et al, 1996). Conversely, a cGMP-gated channel has been found in the rhabdomeric ventral photoreceptor of Limulus (Chen et al, 2001), which may be responsible for at least one component of the light response. CNG channels and a soluble GC are also expressed in Drosophila photoreceptors, although in this case they are implicated in axonal path-finding during development rather than phototransduction (Baumann et al, 1994; Gibbs and Truman, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a putative cyclic nucleotide-gated channel gene has been cloned from Limulus [22]. The mRNA for the channel is expressed in photoreceptors and the protein product was specifically localized in the R-lobe [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The Limulus cascade ends with the opening of cGMP-gated channels which, in this system, can be directly studied in cell-attached and excised patches [19,20]. Photoreceptor cells contain mRNA for a putative Limulus cyclic nucleotide-gated channel protein, and antibodies to the expressed protein specifically label the light-sensitive rhabdomeric lobe [21,22]. Furthermore either intracellular injection of cGMP [23,24] or elevation of cGMP by inhibition of phosphodiesterase [25,26] excites the cell.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that multiple second messenger pathways and channels may mediate the response in Limulus photoreceptors (Nagy 1993). The search for alternative mechanisms has led to physiological and molecular evidence for a cyclic nucleotide gated channel in the light-sensitive membrane of Limulus ventral photoreceptors (Johnson et al 1986;Bacigalupo et al 1991;Chen et al 1999Chen et al , 2001. There is pharmacological evidence for the linkage of the opening of this channel to the PI pathway via a guanylate cyclase (Garger et al 2004), but no biochemical or molecular pathway has yet been identified.…”
mentioning
confidence: 99%